Process mapping as a technical tool for reformulating the preoperative nursing visit instrument for adult patients undergoing cardiac surgery (Research, Society and Development, 2022)
This study is an excerpt from a study on the structuring of the preoperative nursing visit process for adult patients who will undergo cardiac surgery. Its objective is: to apply the process mapping tool in the restructuring of the instrument of the preoperative nursing visit. Methodology: Action research with application of the process mapping tool. Carried out in 2 stages: In the first, the analysis of data from the instrument of preoperative adult visits was carried out and had the year 2018 as a cut-off (n=257). In the next step, the assistant nurses from the surgical center participated in a meeting where they suggested improvements to the process and the instrument through the brainstorming technique. Results: The analysis of the preoperative visits of the adult patient showed a scenario of variability in this process and the meeting with the nurses culminated in the reformulation of the instrument with the participation of the team. Conclusion: The scientific intervention in the reformulation of the instrument aligned with the context of global patient safety recommendations in the preoperative period and with the participation of the subjects who perform the task was ratified.